(untitled) (مجلة المنصور, 2022)
Address Resolution Protocol is an essential protocol deployed over the network session where it maps logical addresses (IP- Internet Protocol) to physical addresses (MAC-Media Access Control). In this paper a multi-agent system is introduced and implemented to prevent known attacks against this protocol (i.e., ARP spoofing and Sniffing) by constructing a cognitive upper layer that sustains the validity and the authenticity of ARP traffic. The presented system is a preemptive system that utilizes domain intelligence to reveal smart attacking methodologies against Spoofing terminologies; the presented system is implemented JADE environment and low level software modules. Results are obtained and analyzed to verify the effect of the approach.